Effective learning in the life sciences : how students can achieve their full potential - Adams, David J. (David James); UK Centre for Bioscience (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons, 2011)
"Draws on experience from a major project conducted by the Centre for Bioscience, with a wide range of collaborators, designed to identify and implement creative teaching in bioscience laboratories and field settings"--Provided by publisher.
Front Matter -- Creativity / David J Adams, Kevin Byron -- Problem Solving b6 (BDeveloping Critical, Evaluative and Analytical Thinking Skills / Tina L Overton -- In the Laboratory / Pauline E Millican, David J Adams -- Fieldwork / Julie Peacock, Julian R Park, Alice L Mauchline -- In vivo Work / David I Lewis -- Research Projects / Martin Luck -- Maths and Stats for Biologists / Dawn Hawkins -- E-Learning for Biologists / Jo L Badge, Jon J A Scott, Terry J McAndrew -- Bioethics / Chris J R Willmott -- Assessment, Feedback and Review / Stephen J Maw, Paul Orsmond -- Communication in the Biosciences / Joanna Verran, Maureen M Dawson -- Bioenterprise / Lee J Beniston, David J Adams, Carol Wakeford -- Appendix -- Index.s
Includes bibliographical references and index.
Print version record.
Keywords: Life sciences -- Study and teaching (Higher); Life sciences -- Study and teaching (Higher) -- Great Britain; Creative teaching; Biological laboratories; Life sciences -- Research; Life sciences -- Fieldwork; NATURE -- Reference; SCIENCE -- Life Sciences -- Biology; SCIENCE -- Life Sciences -- General; Electronic books